Теория и методология управления активами предприятия - Велиева, Э.Э. (Культура народов Причерноморья, 2013)
В статье рассмотрены теоретические и методологические аспекты формирования
политики управления активами предприятия в рамках реализации корпоративной финансовой политики,
ориентированной на увеличение стоимости бизнеса. Также в статье рассморены процесс управления
активами предприятия; основные цели, задачи и принципы управления активами предприятия. Особое
внимание уделено политике комплексного управления активами, в частности, основным условиям при
формировании политики комплексного управления активами предприятия, а также политике
упрфавления необоротными и оборотными активами.
Ключевые слова: необоротные активы, оборотные активы, стоимость бизнеса, управление активами
предприятия, управление финансами, финансовая политика предприятия. У статті розглянуто теоретичні та методологічні аспекти формування політики
управління активами підприємства в рамках реалізації корпоративної фінансової політики,
орієнтованої на збільшення вартості бізнесу. Також у статті розглянуті процес управління активами
підприємства; основні цілі, завдання і принципи управління активами підприємства. Особливу увагу
приділено політиці комплексного управління активами, зокрема, основним умовам при формуванні
політики комплексного управління активами підприємства, а також політиці управління необоротними
і оборотними активами.
Ключові слова: необоротні активи, оборотні активи, вартість бізнесу, управління активами
підприємства, управління фінансами, фінансова політика підприємства. The article deals with the theoretical and methodological aspects of the policy-making asset
management as part of corporate financial policies aimed at increasing the value of the business. The article
also deals with the process of asset management, the main aims, objectives and principles of the asset
management company. Particular attention is paid to the policy of integrated management of assets, in
particular, the basic conditions for policy integrated enterprise asset management, and policy management of
current assets and non-negotiable. This article contains information about the method of optimization of
working capital and fixed assets, in particular the principles of the ratio of assets, the process of optimizing the
structure of a business. This method takes into account the management of assets throughout their set and gives
a complete picture of the structure, dynamics and sources of assets. In the article the process of optimizing the
company's assets is made consistently. In the end, the article provides information on the development and
implementation of financial policy directions to improve the efficiency of asset management.
Keywords: non-current assets, current assets, the cost of business, asset management companies, financial
management, financial policy of the enterprise.